Preserving the rectus femoris and improving limb function after total femoral prosthesis replacement following resection of femoral malignant tumors - Wu, Fan; Fang, Xiang; Yuan, Dechao; Xiong, Yan; Luo, Yi; Zhang, Wenli; Tu, Chongqi; Duan, Hong (Frontiers in Oncology, 2023)
Background: Current research is focused on the factors that influence the maintenance of limb function after total femoral replacement. This retrospective study investigated the difference in functional outcomes in patients with invasion of the rectus femoris vs. an intact rectus femoris that underwent total femoral replacement with a modular total femur prosthesis. Methods: The medical records of patients that underwent total femoral replacement with a modular total femur prosthesis between July 2010 and March 2017 at our institute were retrospectively reviewed. The patients were divided into two groups: Group A had invasion of the rectus femoris and Group B had an intact rectus femoris. Functional status was assessed using the Musculoskeletal Tumor Society Rating Scale (MSTS) and the Harris Hip Score (HHS). Complications were assessed using the International Society of Limb Salvage classification that was published in 2011 and modified in 2014. Results: The mean total MSTS score (23.0±4.8 vs. 17.6±3.1; P=0.02) and the mean total HHS score (80.17±6.24 vs. 55.38±13.30; P=0.001) were significantly higher in patients with intact rectus femoris compared to patients with invasion of the rectus femoris. Patients with an intact rectus femoris achieved significantly better limb function (support and gait) and active range of motion (P<0.05). The overall complication rate was 35.7%. Conclusions: Functional outcomes after total femoral replacement were significantly better in patients with an intact rectus femoris compared to patients with invasion of the rectus femoris, possibly because more muscle mass can be preserved around the femur in patients with an intact rectus femoris.